Analysis of the policy about the handling of functions of land in the city of Semarang (water catchment area of in the Village Sambiroto, district Tembalang) - Harminto, Awang Deny (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2012)
resapan as areas for conservation of green space for residents of thesettlement were made. This triggered the consumptive attitude fromeveryone to meet the needs of the economy and want to get a sense ofprestige from the others. In addition, any encouragement from the plainthat industrial interests. Instead the function is triggered by the existenceof the land party wishing to make a luxury housing in the middle of thecity. The actual land area that is used for resapan, water should not beoverused, as exploriated by the presence of excessive exploration, then thepreviously fertile soil structure and stable and would turn into fault-faultwhich was later unable to hold water in when it rains, so that landpreviously can be categorized into fertile soil barren and haranya elements,in particular the content of humus will increasingly disappear. However,on its implementation under consideration.This research aims at: to formulate alternative policy control over thefunction land ( water catchment area ) in the village sambiroto, sub-districttembalang.From the research can be concluded that:1. Required the manufacture of regulations on the handling of over thefunction of land that is the newest to support perda earlier, namelyperda the city of semarang number 13 year 2006 about the control overthe function of land in the city of semarang.Therefore needs improvement stage the analysis policy in terms ofparticipatory, identification problem policy over the function land andactor its public policy, and need improvement understanding of handlingover the function land in the city of Semarang.